THE INFLUENCE OF INDEPENDENT DIRECTOR CHARACTERISTICS ON TAX MANAGEMENT - Fernando; Oktavia; Hartoni (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2023)
The purpose of this study was to examine the effect of characteristics based on gender, ownership, financial educational background of independent directors as part of the corporate governance organs on tax management in the basic materials sector of companies, industry, consumer cycles and non-consumer cycles in Indonesia. This research uses quantitative methods. The sampling method in this study used a purposive sampling method. The data taken in the annual report is in the form of company financial data for 2019-2021 on the IDX by conducting content analysis to obtain profiles of independent directors. The study used multiple linear regression analysis with unbalanced panel data and REM approach. Based on the tests conducted, gender and years of service have no significant effect on tax management. Meanwhile, the financial education background of independent directors has a significant positive effect on tax management. This research has several limitations. First, this research only focuses on certain sectors. Second, the measurement of the independent director's financial background education variable is only based on the information reported in the annual report, so it can cause bias if background education information is not reported in the annual report.